PERAN NEGATIVE SOCIAL COGNITION DAN SELF-FOCUSED ATTENTION TERHADAP GEJALA GANGGUAN KECEMASAN SOSIAL PADA EMERGING ADULT DI INDONESIA - Steffi Hartanto; Mohammad Adi Ganjar Priadi; Evi Sukmaningrum (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2023)
Â A strong fear of one or more social situations where one might be subject to criticism and scrutiny from others is a sign of social anxiety disorder. Untreated social anxiety disorder symptoms have been linked to risky conduct, including risky sexual activity, abuse of alcohol, tobacco, and other drugs, which peaks throughout the emerging adulthood stage. The key variables that contribute to the symptoms of social anxiety disorder are self-focused attention and negative social cognition, according to a number of cognitive theories. This study looked at the effects of self-focused attention and negative social cognition on social anxiety disorder symptoms in emerging adults in Indonesia. This study's design was a correlational study, and convenience sampling was used to choose participants who were between the ages of 18 and 25 and had at least a high school diploma. The Social Cognitions Questionnaire (SCQ), Self-Consciousness Scale (SCS), and Social Phobia Inventory (SPIN) were made available online to gather data. There were 124 people in all that took part in the study. The results of the multiple regression test reveal that while self-focused attention is not connected with social anxiety, negative social cognition significantly contributes to it. To research the connection between self-focused attention and symptoms of social anxiety disorder in Eastern nations, cultural factors like self-construal can be looked into.